The blood Gospel [compact disc, unabridged] - Rollins, James, 1961- (Rollins, James, 1961- Order of the Sanguines series., 2013)
"An earthquake in Masada, Israel, kills hundreds and reveals a tomb buried in the heart of the mountain. A trio of investigators-- Sergeant Jordan Stone, a military forensic expert ; Father Rhun Korza, a Vatican priest ; and Dr. Erin Granger, a brilliant but disillusioned archaeologist-- are sent to explore the macabre discovery, a subterranean temple holding the crucified body of a mummified girl. But a brutal attack at the site sets the three on the run, thrusting them into a race to recover what was once preserved in the tomb's sarcophagus: a book rumored to have been written by Christ's own hand, a tome that is said to hold the secrets to His divinity. But the enemy who hounds them is like not other, a force of ancient evil directed by a leader of impossible ambitions and incalculable cunning" -- from publisher's web site.